The Inner Freedom to Live. Ken Kesey One Flew Over the Cockoo's Nest - Fekete Sándor (2002)
The basic assumption of my thesis is that the universal appeal of Ken Kesey's novel One Flew Over the Cuckoo's Nest is due to the three main characters having an archetypal nature, i.e. that in each human being there lives a Bromden, a McMurphy, and a Ms. Ratched. To prove my assumption, in the following thesis I intend to analyze the three main figures of Ken Kesey's novel through a method called subject-level analysis: I will look at the three characters as three aspects of our personality. In my thesis I will pay special attention to the figure of Ms. Ratched because of the pedagogical relevance of her personality and behavior.